Normative Approach in the Study of Islamic Law Based On The Thoughts Of Charles J Adams - Hamsah, Yudi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This article discusses Islamic law which is in the spotlight of many groups, especially western scientists who feel moved to study Islamic law with various theories to solve all the problems contained in Islamic law. In this article the author uses library research by collecting various literatures that discuss normative approaches in the study of Islamic law according to Charles J Adams. The results of this study stated that Charles J Adams studied Islam by using his theory, namely using normative and descriptive approaches. The normative approach consists of three parts: the Traditional Missionary Approach, the Irenic (peaceful) Apologetic Approach, the Descriptive Approach, the Philological and Historical Approach, and the Phenomenological Approach. Broadly speaking, the approach offered by Charles J. Adams refers to an approach to Islamic studies based on the values of the basic norms or rules that come from God. The scope of Charles J. Adams' approach includes the Koran, hadith, the prophet Muhammad, pre-Islamic Arabic, Kalam, Sufism, Shia and Popular Religion. One of the thinkers from Indonesia, namely Amin Abdullah, also coined his theory. The first is the problem of understanding Islam, which so far has been understood as a standard dogma. These two types of approaches are theological-normative and historical-empirical approaches are indispensable in viewing the diversity of pluralistic societies.